2021
DOI: 10.1371/journal.pone.0254788
|View full text |Cite
|
Sign up to set email alerts
|

Limb development in skeletally-immature large-sized dogs: A radiographic study

Abstract: Despite the extreme morphological variability of the canine species, data on limb development are limited and the time windows for the appearance of the limb ossification centres (OCs) reported in veterinary textbooks, considered universally valid for all dogs, are based on dated studies. The aim of this study was to acquire up-to-date information regarding the arm, forearm and leg bone development in skeletally-immature large-sized dogs from 6 weeks to 16 weeks of age. Nine litters of 5 large-sized breeds (Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
1
5
1
Order By: Relevance
“…Canine breeds have, however, highly variable progression of skeletal development due to their morphological variability. A recent study performed by Roccaro et al (2021) demonstrated that even breeds of the same size and morphotype displayed different progressions of the limb ossification centres over time. These authors stated that there is a need for further research on the exact time windows of ossification centres and growth plate closure in the different canine breeds as the majority of the information was mainly obtained from old studies performed on small samples of German Shepherds, Greyhounds and Beagles.…”
Section: Introduction Part 3: Methods To Assess Sexual and Skeletal M...mentioning
confidence: 99%
“…Canine breeds have, however, highly variable progression of skeletal development due to their morphological variability. A recent study performed by Roccaro et al (2021) demonstrated that even breeds of the same size and morphotype displayed different progressions of the limb ossification centres over time. These authors stated that there is a need for further research on the exact time windows of ossification centres and growth plate closure in the different canine breeds as the majority of the information was mainly obtained from old studies performed on small samples of German Shepherds, Greyhounds and Beagles.…”
Section: Introduction Part 3: Methods To Assess Sexual and Skeletal M...mentioning
confidence: 99%
“…37 In small-sized breeds, apart from the small-to mid-sized Beagles, 15,38 only a few studies were performed. 31,32,39,40 In addition, most of the studies included only a small sample, often ranging between 10 and 20 dogs, except the studies of Roccaro et al 33 (54 dogs), Yonamine et al 15 (222 dogs) and Smith 34 (nearly 400 dogs). Furthermore, many of these studies were performed for reasons other than age estimation and only included the timing of the first appearance of OCs or the closure of growth plates, without an attempt to define and follow up intermediate stages in a standardised way.…”
Section: Introductionmentioning
confidence: 99%
“…In small‐sized breeds, apart from the small‐ to mid‐sized Beagles, 15,38 only a few studies were performed 31,32,39,40 . In addition, most of the studies included only a small sample, often ranging between 10 and 20 dogs, except the studies of Roccaro et al 33 . (54 dogs), Yonamine et al 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, this technique could not be used in animals younger than 18 months old. Another age estimation method used in mammals is the evaluation of the skeletal age, specifically the radiographic appearance and formation of ossification centers in fore- and hind-limbs bones [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Moreover, these methods are affected by environmental factors, such as nutritional, hormonal, and pathological changes [ 14 , 18 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%